1998
DOI: 10.1074/jbc.273.31.19560
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Microphthalmia in the Inhibition of Melanocyte Lineage Differentiation and of Melanogenesis by Agouti Signal Protein

Abstract: In mouse follicular melanocytes, production of eumelanins (brown-black pigments) and pheomelanins (yellow-brownish pigments) is under the control of two intercellular signaling molecules that exert opposite actions, ␣-melanocyte-stimulating hormone (␣MSH) which preferentially increases the synthesis of eumelanins, and agouti signal protein (ASP) whose expression favors the production of hair containing pheomelanins. In this study, we report that ASP does not only affect mature melanocytes but can also inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(76 citation statements)
references
References 44 publications
5
68
0
3
Order By: Relevance
“…Mitf, Tyr, Tyrp1, Dct, and Si were down-regulated, whereas Tcf4 was upregulated. Previous studies reporting a similar effect of ASP on those genes (15,16,39,40) were consistent with our data. We identified 16 other pigment-related genes whose transcription was repressed by ASP and 2 transcription factors which were upregulated (Lef1 and Tcfap2a/Ap2a).…”
Section: Resultssupporting
confidence: 82%
“…Mitf, Tyr, Tyrp1, Dct, and Si were down-regulated, whereas Tcf4 was upregulated. Previous studies reporting a similar effect of ASP on those genes (15,16,39,40) were consistent with our data. We identified 16 other pigment-related genes whose transcription was repressed by ASP and 2 transcription factors which were upregulated (Lef1 and Tcfap2a/Ap2a).…”
Section: Resultssupporting
confidence: 82%
“…It has been shown that a-MSH also promotes the differentiation of murine melanoblasts into mature melanocytes, and that this induction is also inhibited by ASP. In melanoblasts, the expression of microphthalmia and its binding to the M box regulatory element present in the promoters of melanogenic enzymes, is also inhibited by ASP (72). Taken together, these studies indicate a key regulatory role for ASP in melanocyte differentiation and melanogenesis, and again point to the involvement of microphthalmia in these processes.…”
Section: The Camp Pathway and Agouti Signalingmentioning
confidence: 63%
“…However, little is known about the mechanism of action of ASP on melanocytes. It has been demonstrated that MITF is inhibited by ASP (39). The basic helix-loop-helix transcription factor (ITF2) has been shown to be involved in the action of ASP on pigmentation (40).…”
Section: Figmentioning
confidence: 99%